Who talks to whom? Using social network models to understand debate networks in the European Parliament. (June 2023) - Walter, Stefanie; Kinski, Lucy; Boda, Zsófia
Research into parliamentary speech making–behaviour of Members of the European Parliament (MEPs) usually takes a static perspective. We offer an interactive and dynamic approach that understands parliamentary debates as a relational network phenomenon and investigates MEPs' debate interactions. This allows us to uncover dynamics of inclusiveness and pluralism, self-reinforcing power relationships and transnational policy alliances. Analyzing 11, 408 debate interactions between MEPs using a combination of text and dynamic network analysis, we find that male, senior and influential parliamentarians from powerful member states receive more attention with evidence for a self-reinforcing effect over time. Interestingly, seniority matters more for debate attention than leadership positions. Sharing the same nationality and a similar political leaning also shape debate coalitions with the former being more important than the latter.